Seismic performance of RC frames with concentric internal steel bracing - Youssef, M.A.; Ghaffarzadeh, H.; Nehdi, M. (Engineering structures, 2007)
Steel bracing has proven to be one of the most effective systems in resisting lateral loads. Although its use to upgrade the lateral load capacity of existing Reinforced Concrete (RC) frames has been the subject of numerous studies, guidelines for its use in newly constructed RC frames still need to be developed. In this paper, the efficiency of using braced RC frames is experimentally evaluated. Two cyclic loading tests were conducted on a moment frame and a braced frame. The moment frame was designed and detailed according to current seismic codes. A rational design methodology was adopted to design the braced frame including the connections between the brace members and the concrete frame. Test results showed that the braced frame resisted higher lateral loads than the moment frame and provided adequate ductility. The adopted methodology for designing the braced frame resulted in an acceptable seismic performance and thus represents the first step in the development of design guidelines for this type of frames.